Sachunterricht in der Informationsgesellschaft - Becher, Andrea; Blumberg, Eva; Goll, Thomas; Michalik, Kerstin; Tenberge, Claudia (Probleme und Perspektiven des Sachunterrichts, 2022)
As part of the information and knowledge society, children and adults are both affected by and involved in the digital transformation. The extent to which information and knowledge can actually be accessed, used and shaped by everyone is a question of educational theory and subject didactics. Pupils, teachers, students and trainee teachers must be supported in opening up the possibilities and limits of the information society, in reflecting on them and in recognising and developing options for action, orientation and skills. In the present volume, subject matter teaching in the information society is examined from the perspectives of subject matter didactic reconstruction, media education and informatics education; the question of appropriate locations, media and technologies is also addressed, as are projects in university teacher training and perspective-related approaches. (DIPF/Orig.)